Improvement in Cardiovascular Autonomic Neuropathy After High-Dose Vitamin D Supplementation in Patients With Type 1 Diabetes - Silva, Lilian de Souza D’Albuquerque; de Queiroz, Natércia Neves Marques; de Melo, Franciane Trindade Cunha; Abrahão Neto, João Felício; Janaú, Luísa Corrêa; de Souza Neto, Norberto Jorge Kzan; de Lemos, Manuela Nascimento; de Oliveira, Maria Clara Neres Iunes; de Alcântara, Angélica Leite; de Moraes, Lorena Vilhena; da Silva, Wanderson Maia; de Souza, Ícaro José Araújo; et al. (Frontiers in Endocrinology, 2020)
Background: Cardiovascular autonomic neuropathy (CAN) is associated with diabetes mellitus, increasing morbidity and mortality. Some cross-sectional studies associated CAN with low 25-hydroxyvitamin D levels. The aim of our study was to evaluate the effect of high-dose vitamin D (VD) supplementation on CAN in Type 1 Diabetes Mellitus (T1DM) patients. Methods: We performed a prospective study with 23 patients diagnosed with T1DM and CAN. Subjects with VD levels <30ng/mL received 10,000 IU/day; the ones with VD levels between 30-60 ng/mL were given 4,000 IU/day for 12 weeks. Results: There was an improvement in CAN parameters related to resting heart rate variability, such as time domain parameters [Maximum RR interval (0.77 ± 0.11 vs 0.94 ± 0.51 sec, p <0.05), Mean length of regular RR intervals (0.71 ± 0.10 vs 0.76 ± 0.09 sec, p <0.05) and Standard deviation of all NN intervals (0.02 ± 0.01 vs 0.03 ± 0.02 sec; p <0.01)] and frequency domain parameters [Low Frequency (1.9 ± 0.5 vs 2.5 ± 0.9 sec, p < 0.001), Total Power (2.5 ± 0.4 vs 2.8 ± 0.6 sec, p <0.05)]. In addition, there was a correlation between absolute VD level variation and posttreatment High Frequency (%), as well as among percent variation in VD level and end-of-study Low Frequency/High Frequency ratio (r=0.6, p<0.01; r= -0.5, p<0.05, respectively). Conclusion: Our pilot study is the first to suggest a strong association between high-dose vitamin D supplementation and improved cardiovascular autonomic neuropathy in T1DM patients. It occurred without any variation in HbA1C, blood pressure levels, lipids and insulin dose. Trial registration: ISRCTN32601947. URL: http://www.isrctn.com/ISRCTN32601947.